Respons Mahasiswa terhadap Penerapan Kurikulum Merdeka - Vera Astuti; Selamat Husni Hasibuan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Independent Curriculum is a transitional curriculum after the COVID-19 crisis. Independent Curriculum aims to make students have learning independence, think critically, innovatively and creatively. This requires students to be more active (student oriented), able to solve personal and other problems, and able to produce certain projects as the final output of the learning process. Campuses are free to design curricula for learning systems and lecture systems to realize these goals. This research focuses on seeing student responses in the application of the Independent Curriculum in terms of the learning system and lecture system. The research method used is descriptive qualitative with an unstructured interview method. The results showed a positive student response to the implementation of the Independent Curriculum even though there are notes that can be used as reference material for improving curriculum development in the future.